Bamboo's tissue structure facilitates large bending deflections. (4th October 2021) - Chen, Qi; Razi, Hajar; Schlepütz, Christian M; Fang, Changhua; Ma, Xinxin; Fei, Benhua; Burgert, Ingo
Abstract: Bamboo is becoming increasingly popular as an engineering material and source of bio-inspiration for instance in architecture and for the manufacture of a variety of woven products. Besides the properties of bamboo products for construction purposes, the bending deformability of thin bamboo slivers is of interest, as it appears that extraordinary large deflection can be achieved. To unravel the underlying mechanisms that may contribute to the high deformability at the tissue and cell level, bending deflection tests and additional in situ experiments were performed to record the deflection of bamboo slivers in dependence of the tissue composition and the deformations of individual cells. For the latter, a simple bending deflection setup was used employing micro-CT measurements to analyze the deformation of individual parenchyma cells (PCs), fiber bundles and vessel elements at different stages of bending deformation of the bamboo slivers. The results showed that the degree of displacement and the characteristic fracture behavior strongly depend on the volume fractions of PCs and fibres determined by the position in the bamboo culm. For slivers with a sufficiently high fibre volume content, the very high bending deformability could be facilitated by the deformation of PCs, which are squeezed between the fibre bundles during increasing bending deflection.